Joint Venture (JV) dengan Skema Special Purpose Vehicle (SPV) untuk Penanaman Modal Asing di Indonesia - Darin Sevira, Jihan (UNES Law Review, 2023)
Foreign investment in one of the countries in the South East Asia, Indonesia can be executed in the structure of joint venture (JV) scheme between foreign investors and domestic investors. This investment can be conducted in the form of a special purpose vehicle (SPV) whereass a new company will be formed to accommodate this JV collaboration. This paper analyzes the SPV based on regulations in Indonesia and SPV in the case of JV schemes based on the relevant regulations in terms of foreign investment in Indonesia. In the end, the researcher concluded that joint ventures in Indonesia have been regulated in Law Number 25 of 2007 concerning Investment, however regarding SPV, the regulations that regulates are still inconsistent and inadequate in Indonesia.